Pengaruh Model Discovery Learning Berbantuan Media Anyaman Terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Nasifatul Baroroh; Ratri Rahayu; Himmatul Ulya (Journal Prakarsa Paedagogia, 2019)
The aim of this research was to test the effect of discovery learning models using matting media toward students' understanding of mathematical concepts. The result of this research showed that (1) the average ability of students' understanding of mathematical concepts after applying discovery learning models using matting media was better than before; (2) amount 70% students reached minimal completeness criteria (MCC); (3) there was difference in the proportion of students who reach MCC before being taught discovery learning models assisted by matting media with the proportion of students who reach MCC have been given learning. The use of matting media in mathematics learning with discovery learning models has an impact on the ability of students' understanding of mathematical concepts. In the steps of the discovery learning model, namely data collection, students explore knowledge by weaving to form a unit square. The data was then processed by students to find the area of the plane with its own knowledge.